SISTEM REWARD DAN PUNISHMENT SEBAGAI PEMICU DALAM MENINGKATKAN KINERJA KARYAWAN - Ludfi Ferry Wijaya (Journal MISSY (Management and Business Strategy), 2021)
A company certainly really wants employees to have good performance and have the motivation to work continuously so that the company is able to become a place to work that can make employees grow. There are various ways that can be done to improve employee performance. By using the right way will be able to improve employee performance better. The way that can be done to improve the performance of employees is to provide rewards when employees can achieve their goals and sanctions (punishments) when employees are negligent in their work. Giving punishment or reward is one of the ways used by companies to always motivate their employees to do their best for the company. The purpose of this reward and punishment system is to continue to encourage outstanding employees.